Pembelajaran Jigsaw Konsep Tata Surya melalui Pendekatan Real Learning Guna Meningkatkan HOTS Siswa - Susiana S. (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2020)
This study aims to determine the improvement of students' High Order Thingking Skills (HOTS) abilities after Jigsaw cooperative learning is applied through the Realistic Learning science approach. This research is a classroom action research with 3 cycles including planning, action implementation, observation and reflection. Data collection techniques in this study were tests, student activity observation sheets, and teacher activity observation sheets. The planning stage in the form of activities (1) making learning tools, (2) making observation sheets and ways of observation, and (3) compiling learning evaluation tools in the form of essay test questions based on cognitive domains C4, C5, and C6. Based on the data obtained by the results of the study are (1) the activity of the first cycle teacher category enough with a score of 47, the second cycle category is good with a score of 54, and the third cycle enough category with a score of 64, (2) the activity of the first cycle category students is enough with a score of 16, the second cycle category is good with a score of 18, and the third cycle is very good category with a score of 21, and (3) the average score of the students' essay tests in the first cycle is 64.78, the second cycle is 72.8, and the third cycle is 82 , 4. It was concluded based on the results of the research that showed that the application of Jigsaw cooperative learning through the Realistic Learning approach could improve the learning activities and learning outcomes of students which illustrated an increase in the High Order Thingking Skills (HOTS) of students in class IX.C of SMP Negeri 3 Kepahiang.